Comparison of Safety and Efficacy of Two Different Chemotherapy Dosing Schedules Used in Concurrent Chemoradiation of Head and Neck Cancer: A Retrospective Experience from a Tertiary Cancer Care Institute of Eastern India - Bhanja, Sayoni; Lahiri, Debarshi; Roy, Sanjoy; Maji, Tapas; De, Palas (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Concurrent chemoradiation has demonstrated improvements in local control and survival in various multi-institutional trials and has become the standard of care for locally advanced head and neck cancers. Platinum-based chemotherapy has shown the greatest benefit, with no significant difference observed between mono- or polychemotherapy. Despite a general consensus that platinum-containing regimens are optimal, the optimal dose schedule remains unclear. This study aimed to assess the efficacy and toxicity of concurrent weekly cisplatin with radical radiotherapy and compare two different chemotherapy dosing schedules used in concurrent chemoradiation for head and neck cancer. Materials and Methods: The records of 62 eligible patients with locally advanced (T3-4a, N1-2) squamous cell carcinoma of the oropharynx, hypopharynx, and larynx registered between 2016 and 2020 at a regional cancer center in India were analyzed from the hospital database after obtaining approval from the Institutional Ethical Committee and informed consent from all eligible patients. One group of patients (Group A) received concurrent chemoradiation with weekly cisplatin (40 mg/m2) and radiotherapy to a dose of 66 Gy delivered in 33 fractions over six and a half weeks. The other group of patients (Group B) received cisplatin (100 mg/m2) on a three-weekly schedule (Days 1, 22, and 43) with the same radiation schedule. Results: There was no significant difference in baseline characteristics between the two groups (p-value ≥ 0.05). Although complete response occurred more frequently in the three-weekly group compared to the weekly cisplatin group at follow-up of 6 weeks (67.7% vs 61.3%), 6 months (80.6% vs. 67.7%), and 12 months from the completion of concurrent chemoradiation (CCRT) (78.9% vs 65%), this difference was not statistically significant (p-value ≥ 0.05). No statistically significant differences were found in terms of both acute toxicities (anemia, leukopenia, mucositis, dermatitis, upper gastrointestinal toxicities, dysphagia) and late toxicities (laryngeal edema, dry mouth, and edema of the skin of the neck) when weekly concurrent chemoradiotherapy was compared to three-weekly chemoradiotherapy (p-value ≥ 0.05). Conclusion: The weekly chemotherapy regimen can be delivered safely on a day-care basis and can be helpful in settings with limited logistics and significant patient burden.